2011
DOI: 10.1093/arclin/acr069
|View full text |Cite
|
Sign up to set email alerts
|

The Ecological Validity of Clinical Tests of Visuospatial Function in Community-Dwelling Older Adults

Abstract: Little is known about the relation between measures of visuospatial function and daily functioning in community-dwelling older adults. The current study addresses this gap in the literature. Forty individuals with mean (SD) age and education of 78.4 (7.5) and 11.9 (2.6) years, respectively, completed a battery of neuropsychological measures including traditional tests of visuospatial function, a test of visuospatial function with verisimilitude, and performance-based measures of global daily functioning and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The weakest correlations found between cognitive and functional measures were related to visuospatial skills (Mattis Construction and Clock Drawing Test). However, previous studies have found significant associations between functional performance and visuospatial skills (Davies et al, 2011; Farley et al, 2011). This divergence reflects the need for components directed at the evaluation of activities strongly related to the processing of spatial information.…”
Section: Discussionmentioning
confidence: 88%
“…The weakest correlations found between cognitive and functional measures were related to visuospatial skills (Mattis Construction and Clock Drawing Test). However, previous studies have found significant associations between functional performance and visuospatial skills (Davies et al, 2011; Farley et al, 2011). This divergence reflects the need for components directed at the evaluation of activities strongly related to the processing of spatial information.…”
Section: Discussionmentioning
confidence: 88%
“…Different aspects of executive functions such as planning, cognitive flexibility, and selective attention were associated with transportation in the study of Jeferson et al (2006). Deficits in these functions were associated with impairment in “visually” dependent activities such as driving, orientation, and transport use ( Silva et al, 2009 ; Farley et al, 2011 ). However, despite the expected relationship between visuospatial abilities and the ability to travel long distances, few studies have found a significant direct association between the neuropsychological performance and its functional counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…However, other cognitive functions may contribute to specific aspects of ADL. Cognitive measures of spatial processing predicted participants’ performance in an ecological measure of visuospatial abilities in which the subject had to estimate distances, positions, and directions in a “real-life” setting developed by Farley et al (2011) . Activities demanding communicative skills were related to semantic process and language ( Razani et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in EPT test takers solve problems in seven domains, such as food preparation, medication usage, and telephone communication. All three measures have been previously validated, established as reliable, and are widely used to assess IADL competence (Burton, Strauss, Bunce, Hunter, & Hultsch, 2009; Edwards et al, 2005b; Farley, Higginson, Sherman, & MacDougall, 2011; Goverover, Genova, Hillary, & DeLuca, 2007; Jobe et al, 2001; Pressler et al, 2011; Yam & Marsiske, 2013). Performance across these three IADL tests is intercorrelated (e.g., Sartori et al, 2012), and each is associated with UFOV performance (Owsley et al, 2002; Sartori et al, 2012).…”
mentioning
confidence: 99%